2009
DOI: 10.5465/ambpp.2009.44268008
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Foundations of Dynamic Capabilities: Reflexion and Reflection in Strategic Management.

Abstract: In recent years, there has been a move to identify the behavioral foundations underpinning the evolutionary and economic fitness of the enterprise. Indeed, the dynamic capabilities project now occupies center stage in the field of strategic management. Yet the accounts developed thus far-like much of the field's theory and research more generally-are predicated upon a cold cognition logic that downplays the significance of emotional/affective and nonconscious cognitive processes for strategic adaptation. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
315
0
18

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 212 publications
(336 citation statements)
references
References 106 publications
(173 reference statements)
3
315
0
18
Order By: Relevance
“…Prior studies showed that managerial capability directly stimulates organizational innovation; however, this was not supported in our study, as managerial capabilities need to be engulfed within adaptive capabilities prior in order to stimulate organizational innovation. Managerial style also showed a positive relationship with adaptive capability, which is justified by the literature [32,139], where managers sense the opportunities and threats and then reconfigure the firm's sources and capabilities in order to sustain the competitive advantage. Also, management style and people development play a vital role in organizational innovation if managers and employees are provided with such training and knowledge, which will sustain the competitive advantage by carefully scanning the competitors and anticipating future trends.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Prior studies showed that managerial capability directly stimulates organizational innovation; however, this was not supported in our study, as managerial capabilities need to be engulfed within adaptive capabilities prior in order to stimulate organizational innovation. Managerial style also showed a positive relationship with adaptive capability, which is justified by the literature [32,139], where managers sense the opportunities and threats and then reconfigure the firm's sources and capabilities in order to sustain the competitive advantage. Also, management style and people development play a vital role in organizational innovation if managers and employees are provided with such training and knowledge, which will sustain the competitive advantage by carefully scanning the competitors and anticipating future trends.…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, the development of a firm relies on the existing experience and learning of the managers, since they are the enablers of organizational capability [31]. Managerial capability relies on more than just cognition; it also requires the understanding of human emotions, and non-cognitive processes that develop and enable strategic adaption behaviors (adaptive capability) in volatile environments [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…If indeed DC must consist of several elements, such as the "sensing-seizing-reconfiguring" tripod (Teece, 2007), then one could reasonably argue that our cognition variables capture the first leg of the tripod, "sensing the environment" (Pavlou & El Sawy, 2011: 239), and that our asset reconfiguration variables provide a good proxy of the last leg, "reconfiguring assets and structures to maintain competitiveness" (Hodgkinson & Healey, 2011: 1501. In this context, this study would demonstrate that adaptation to shifting conditions can occur either without superior "sensing" (C3 and C4 in Table 3), or without increasing the pace of "reconfiguring" (C1).…”
Section: Revisiting An Old Question: Dynamic Capabilities What Are Tmentioning
confidence: 99%
“…Further illustrating the efficacy of this third framing strategy of fostering broader conversations with more specialist audiences, I turn now to consider finally one of my relatively recent papers on the psychological foundations of strategic management (Hodgkinson and Healey, 2011).…”
Section: Fostering Broader Conversations With More Specialist Audiencesmentioning
confidence: 99%
“…Drawing on the insights of state-of-the-art-advances that have taken place in the affective sciences over the past two decades, our goal in the Hodgkinson and Healey (2011) paper, which appeared in a special issue of Strategic Management Journal devoted to 'the psychological foundations of strategic management' was to move along the conversation on cognition and strategy away from an affect-free conception of strategists as cognitive misers (and sensemakers), toward a 'hot' cognition alternative, one that recognizes that strategists are ultimately, "governed by thoughts and feelings: always boundedly rational, but manifestly driven by emotion" Healey, 2011, P. 1512). Using the much-cited dynamic capabilities paper of Teece (2007) as an overarching framework, our analysis demonstrated systematically how each of the psychological foundations underpinning Teece's (2007) framework are predicated on psychological conceptions that are outmoded when viewed in the light of more recent advances in social cognitive neuroscience (e.g.…”
Section: Fostering Broader Conversations With More Specialist Audiencesmentioning
confidence: 99%